Is the Jigsaw Model Still Relevant for Improving Mathematical Ability? Meta-Analysis Studies - Soebagyo, Joko; Maarif, Samsul; Suhendri, Huri; Leonard, Leonard (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2024)
The Jigsaw learning model focuses on student activities in learning in general and also has an influence on students' mathematical abilities, but there are also some that do not have a significant influence. This research attempts to answer how much influence the Jigsaw model has based on the desired categorical variables. Therefore, meta-analysis research is needed to provide comprehensive and in-depth conclusions about the application of the Jigsaw model to students' mathematical abilities. Comprehensive Meta-Analysis (CMA) is used to evaluate a property's value based on comparisons to similar properties in the same area. Data was obtained from Publish or Perish (PoP) with a total of 500 articles from 2010 to 2023 with the Google Scholar database. The number of journals that meet the requirements and will be analyzed is 30 sample articles with a total of 1252 students. The moderator variables in this study consider country, education level, sample size and publication source. Based on research findings, the Jigsaw model has a significant influence on numeracy skills (P-value 0.05), with an effect size of 1.146 which is classified as very high based on fixed effects and a standard error of 0.045. The research results show that the Jigsaw model is still relevant for improving students' mathematical abilities, especially at the elementary school level. This meta-analysis study reveals that there is no difference in the results of implementing the Jigsaw model on students' mathematical abilities in all country categories.